PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN KONSUMEN PADA RESTAURAN IGA BAKAR MAS GIRI PURWOKERTO - Kusuma Putra, Aris Ginajar; Suyoto, Suyoto (Media Ekonomi, 2017)
This study amied to investigate the effect of product quality and service quality in the restaurant ribs grilled Mas Giri Purwokerto throught testing either simultaneously or partially. The method used in the analiysis method used is multipele linear regression with the significant level (á¾³) of lees than 0.05. These result indicate that the product quality and quality of service simultaneously affect coustemer satisfaction, product quality and service quality in partial satisfaction of the coustemer, with a significant value of 0,00 and 0,00 is less than 0,05. Keywords : Quality Products, Quality Service and Coustemer Satisfaction.